THE INFLUENCE OF A SPECIFIC FLAT KNITTING EQUIPMENT ON THE RESISTANCE OF KNITTED MATERIALS MADE OF HIGH-STRENGTH YARNS TO MECHANICAL DAMAGE (PIERCING WITH A ROD AND PRESSING WITH A BALL) - ДМИТРИК, ОКСАНА; ГАЛАВСЬКА, ЛЮДМИЛА; ХАРЧЕНКО, ЮЛІЯ (Technologies and Engineering, 2024)
Purpose. To study the influence of peculiarities of manufacturing with the use of flat knitting equipment of two types (with and without sinkers) of knitted material of the plain interloping made from high-strength yarns on its resistance to mechanical damage (particularly, piercing with a rod and pressing with a ball). Methodology. To determine specifics of the resistance of knitted materials to mechanical damage such as piercing with a rod and pressing with a ball, actual standardized research methods were used. The study of the resistance to piercing with a rod and pressing with a ball was carried out using an electronic tensile tester KT-7010AZ. An active one-factor experiment was conducted to determine the influence of the knitting density and the type of flat-knitting equipment on the characteristics of knitted fabrics' resistance to mechanical damage in accordance with the selected type of flat-knitting equipment. The method of linear regression analysis was used to process the experimental data and construct graphs and diagrams of mechanical effects in the traditional planning of an active one-factor experiment implementing the tools of Microsoft Excel. The results. In the course of the research, it was found out that the resistance to piercing with rod and pressing with a ball of knitted fabrics made of high-strength yarns is influenced by the type of yarns chosen, as well as by the type of flat-knitting equipment, the jersey structure depth and knitting density. At the same time, knitted fabrics produced with the use of flat-knitting equipment without platens demonstrate a higher level of resistance to the studied indicators of mechanical damage. In particular, it was not possible to establish the tensile strength of a knitted material produced from high molecular weight polyethylene yarns to resist the ball punching, since the pressure exceeded 5000N, with the measurement scale of the tensile machine being 5000N. The nature of deformation of test samples under the influence of the force caused by the rod piercing and ball pressing was analyzed. The processes of piercing and pressing are preceded by the tear-off of a single thread in the knitted material structure. However, in the case of para-aramid yarns, the loops are immediately released as a result of the yarn rupture and damage to the structure wholeness. Scientific novelty. It has been established that the value of resistance to piercing with a rod and pressing with a ball of knitted fabric is influenced not only by the selected type of high-strength yarns and knitting density, but also by the presence of platens in the looping process. The nature of influence of a flat-knitting equipment type (with and without sinkers) and the knitting density of knitted materials of a plain weave made from high-molecular-weight polyethylene and para-aramid yarns on the value of resistance to mechanical damages was as well specified. Practical significance. The mathematical dependencies obtained during the implementation of an active single-factor experiment of the research allow us to calculate the value of resistance to piercing with a rod and pressing with a ball and to select rational manufacturing parameters (type of high-strength yarns, type of flat knitting equipment, depth of jersey structure) in accordance with the required level of resistance of knitted fabrics to the studied indicators of mechanical damage, and to determine the rational parameters of manufacturing knitted fabrics.